Rethinking vegetarianism: Differences between vegetarians and non-vegetarians in the endorsement of basic human values. - John B Nezlek (PLoS ONE)
Differences between the basic human values of vegetarians and non-vegetarians were examined in three studies of samples of adults drawn from general populations, one in the US and two in Poland. Vegetarians were oversampled in the US study (514 vegetarians, 540 non-vegetarians) and in one study in Poland (301 vegetarians, 335 non-vegetarians). In the other Polish study, there 68 vegetarians and 1943 non-vegetarians. Values were measured using Schwartz's Portrait Value Questionnaire. Across all three studies, Benevolence, Security, and Conformity values were significantly less important for vegetarians than they were for non-vegetarians, although the difference for Conformity was marginally significant (p < .10) in the US study. Across all three studies, vegetarians also endorsed Tradition values less strongly than non-vegetarians, although this difference was not statistically significant in the US study (p = .12). Across all three studies, vegetarians endorsed Stimulation, Achievement, and Power values more strongly than non-vegetarians did. There was only one value, Self-direction, for which the difference between vegetarians and non-vegetarians varied between the two countries. In the US, Self-direction values were more important for non-vegetarians than they were for vegetarians, whereas in Poland the difference was in the opposite direction. Across the three studies, there were only a few instances in which differences between vegetarians and non-vegetarians varied as a function of respondents' gender. These results suggest that following a vegetarian diet represents a manifestation of values that emphasize independence and individuality, a possibility that is somewhat at odds with how vegetarianism is often discussed.